O controle cooperativo de constitucionalidade das normas através das audiências públicas e da atuação do Amicus Curiae na jurisdição constitucional - Oliveira, Jadson Correia de (2014)
This paper has as goal to examine the thesis of Peter Häberle about the open society of interpreters of the Constitution, i.e., the pluralization of the debate and the constitutional process. The starting point for such a study is due to the recent positions taken by the Supreme Court (STF) based on democratic participation in their decisions, such as holding public hearings as well as enabling that amici curiae participate in the course of the objective processes of constitutional control. The study presents each of the major themes of the German jurist thesis, such as: legitimacy of law and the role of interpreters of the Constitution, because, as Häberle declared, there is no rule unless the interpreted one, therefore the extreme concern about the interpreter, taking special attention, in the current constitutional process: in the Brazilian tradition, the amicus curiae, the reinterpretation of the principle of legality after the new constitutionalism, with emphasis on the period after the second world war, the need to carry out the constitutional process in accordance with the evolution of the society itself, about its values (time and Constitution), the evolutive interpretation of the Constitution, in order not to fossilize the law and/or not allowing that it be far away from the whole society. By logical consequence, it is mandatory to near law and society, wich may be done by adopting non majority position by the Court that helds that the constitutional process. It is also to be noted that the opening of the constitutional process, although it is a trend that has been applied in many jurisdictions, even due to the approximation of judicial review models (diffuse and concentrated), receives hard criticism, mainly because of the social openness to the Constitution, either if it is held by a Constitutional Court or by a Supreme Court. This happens due to the occurence of such activity at the level of problematic interpretation issue, which permeates the concerning results, either they are majority or not. This paper uses, as an example of the theory`s application, the analysis of extracts from the vote of Celso de Mello, one of the Supreme Court ministers, about the recognition of homo-afective unions, delivered in ADPF 132/RJ.